SEHATI PROGRAM (Integrated Digital Education and Health Services System) in Sogo Village, Kedung District, Tuban Regency, Blora Regency, Central Java, and Ngampel Village, Kapas District, Bojonegoro Regency, East Java. - Frestina Bhakti Herwidyaningsih; Cipnal Muchlip; Aziz Safi'i; Yusuf Efendi; Angger Anugerah Hadi Sulistyo (LPPM ISTeK ICsada Bojonegoro, 2026)
The SEHATI Program (Integrated Digital Education and Health Service System) is a community empowerment initiative utilizing digital technology to improve health literacy and access to health services in Sogo Village, Kedungtuban District, Blora Regency, Central Java, and Ngampel Village, Kapas District, Bojonegoro Regency, East Java. This program integrates digital health education, community assistance, and the use of health information systems to support effective and sustainable health services. The implementation methods include socialization activities, digital media training, and collaboration with local health workers. The results indicate increased community knowledge, improved access to health information, and strengthened community participation in maintaining independent health practices. The SEHATI Program is expected to serve as a model for integrated digital health services in rural areas.